Dog body size in Siberia and the Russian Far East and its implications. (1st August 2020) - Losey, Robert J.; Nomokonova, Tatiana; Kosintsev, Pavel A.; Bachura, Olga P.; Gusev, Andrei V.; Vasyukov, Dmitry D.; Savinetsky, Arkady B.; Tishkin, Alexey A.; Grushin, Sergei P.; Gorbunov, Vadim V.; Papin, Dmitri V.; Sablin, Mikhail V.; et al.
Abstract: Body size is correlated with many critical behavioral and developmental patterns in carnivores, including domestic dogs. The body masses and bite forces of archaeological dog remains from Siberia and the Russian Far East were estimated to make inferences regarding their behaviors and capacitis. The dogs date from ∼10, 000–100 cal. BP and derive from archaeological sites spanning from steppe environments in the south to tundra regions of the northern Arctic. The dogs exhibit a four-fold difference in body mass, ranging from 7.6 to 32.5 kg, but have a mean body mass of only 16.4 kg. Bite forces are around only half those of modern wolves, indicating that the dogs had greatly reduced abilities to grasp and masticate prey and food items. The dogs exhibit a slight decrease in body size through time, perhaps due to human selection or greater survival rates for smaller individuals in human-dominated food environments. Dog body size variance within individual archaeological sites was as high as in a sample of modern wolves from throughout the study area, suggesting little strict human control over body size. No correlation was found between body size and site latitude, suggesting that Bergmann's rule does not hold for these canids. Human shelters may provide a buffer against low temperatures that might favour larger body sizes at high latitudes. About 90% of the analyzed dogs have estimated body masses less than 21.5 kg, suggesting most were best adapted for procuring prey smaller than themselves—the dogs were not capable of taking down larger prey without the assistance of humans. Estimated dog body masses cannot eliminate the possibility that many of the animals were used for pulling sleds, and nearly all were capable of packing modest loads on their backs. Livestock guarding dogs are not well-evidenced by the body mass data, but herding dogs are a possibility in all of the pastoral or agricultural settings analyzed. Graphical abstract: Image 1 Highlights: Body masses and bite forces were estimated for 199 archaeological dog remains from Siberia and the Russian Far East. The dogs' body masses range from 7.6 to 32.5 kg, with a mean of 16.4 kg. The dogs' bite forces are around half those of modern wolves. The dogs exhibit a slight decrease in body size through time. Many of the dogs were of sufficient size to pull sleds, and all could have carried packs.